2021
DOI: 10.1038/s42003-021-01708-y
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like 3 affects zebrafish spermatogenic cells directly and via Sertoli cells

Abstract: Pituitary hormones can use local signaling molecules to regulate target tissue functions. In adult zebrafish testes, follicle-stimulating hormone (Fsh) strongly increases the production of insulin-like 3 (Insl3), a Leydig cell-derived growth factor found in all vertebrates. Little information is available regarding Insl3 function in adult spermatogenesis. The Insl3 receptors Rxfp2a and 2b were expressed by type A spermatogonia and Sertoli and myoid cells, respectively, in zebrafish testis tissue. Loss of insl3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 78 publications
3
9
0
Order By: Relevance
“…The Insl3 receptors, rxfp2a and rxfp2b , expressed in type A spermatogonia and Sertoli cells/myoid cells, respectively, were also decreased in the cyp17a1 -/-; ar -/-; npgr -/- fish compared with that in the control males ( Figure 6B and C ), suggesting compromised Insl3 signaling in cyp17a1 -/-; ar -/-; npgr -/- fish. The upregulated expression of the retinoic acid-degrading enzyme, cyp26a1 , decreased GSI and disrupted testis morphology in the cyp17a1 -/-; ar -/-; npgr -/- fish ( Figures 6D and 4H and I), correlating with the observations in the insl3 -/- males ( Crespo et al, 2021 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The Insl3 receptors, rxfp2a and rxfp2b , expressed in type A spermatogonia and Sertoli cells/myoid cells, respectively, were also decreased in the cyp17a1 -/-; ar -/-; npgr -/- fish compared with that in the control males ( Figure 6B and C ), suggesting compromised Insl3 signaling in cyp17a1 -/-; ar -/-; npgr -/- fish. The upregulated expression of the retinoic acid-degrading enzyme, cyp26a1 , decreased GSI and disrupted testis morphology in the cyp17a1 -/-; ar -/-; npgr -/- fish ( Figures 6D and 4H and I), correlating with the observations in the insl3 -/- males ( Crespo et al, 2021 ).…”
Section: Discussionsupporting
confidence: 71%
“…and C), suggesting compromised Insl3 signaling in cyp17a1-/-;ar-/-;npgr-/-fish. The upregulated expression of the retinoic acid-degrading enzyme, cyp26a1, decreased GSI, disrupted testis morphology in the cyp17a1-/-;ar-/-;npgr-/-fish (Figure6D, 4H and I) correlated with the observations in the insl3-/males(Crespo et al, 2021).The sperm fertilities of the ar+/+ males and ar-/-males after treatment with DHP were also measured. Unfortunately, both experiments showed impaired fertility after DHP treatment via artificial fecundation assays with WT females (Figure3-figure supplement 1).…”
supporting
confidence: 68%
“…Figure S3). The low insl3 expression in the germ cell-depleted testis could be explained by the function of Insl3 acting as germ cell survival factor (Crespo et al, 2021). Moreover, the stimulatory effect of Fsh on insl3 mRNA levels was shown to be inhibited by Amh (Skaar et al, 2011), which was strongly downregulated only in the maturing fertile males.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to sterile males, the maturing fertile males displayed strongly upregulated insl3 expression that was correlated with the wnt5a transcript levels (Supporting Information: Figure ). The low insl3 expression in the germ cell‐depleted testis could be explained by the function of Insl3 acting as germ cell survival factor (Crespo et al, 2021). Moreover, the stimulatory effect of Fsh on insl3 mRNA levels was shown to be inhibited by Amh (Skaar et al, 2011), which was strongly downregulated only in the maturing fertile males.…”
Section: Discussionmentioning
confidence: 99%
“…Here, tissue culture and in vivo experiments revealed that Insl3 is highly sensitive to Fsh (but not Lh) stimulation and induces proliferation of undifferentiated spermatogonia, independently form androgens [ 68 , 88 , 90 , 91 ]. A recent knock-out study in zebrafish further succeeded in starting to unravel the downstream actions of insl3 [ 92 ]. The researchers showed that besides direct stimulation of undifferentiated spermatogonia via the Rfxp2a receptor, Insl3 can utilize several paracrine mechanisms to regulate the spermatogenic process, especially via Sertoli cell actions (retinoic acid and proliferator-activated receptor gamma signaling).…”
Section: Discussionmentioning
confidence: 99%